2004
DOI: 10.1093/humrep/deh112
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HRT on prognostic factors for breast cancer: a systematic review after the Women's Health Initiative trial

Abstract: In view of these data, the current clinical message to patients should be changed: one can no longer declare that breast cancers developed while using HRT are of better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 49 publications
1
19
2
3
Order By: Relevance
“…The study was underpowered to access the effect on grade, histology and hormone receptor status. A recent systematic review of 25 studies that evaluated breast cancer risk factors and prognostic indicators concluded that the WHI study is in contradiction to most published observational studies (Antonie et al, 2004). Our results also appear to contradict the WHI results.…”
Section: Discussioncontrasting
confidence: 94%
“…The study was underpowered to access the effect on grade, histology and hormone receptor status. A recent systematic review of 25 studies that evaluated breast cancer risk factors and prognostic indicators concluded that the WHI study is in contradiction to most published observational studies (Antonie et al, 2004). Our results also appear to contradict the WHI results.…”
Section: Discussioncontrasting
confidence: 94%
“…Most observational studies indicate such an association, whereas the Women's Health Study randomized trial found HRT oestrogen -progestin use to be associated with larger and lymph node-positive tumours (Antoine et al, 2004). If HRT is linked to less aggressive tumours, our finding of a poorer survival among obese women only among HRT users could be explained as follows: the beneficial prognostic effect seen by HRT in most observational studies is confined to lean women, in whom the HRT effect is most pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rosenberg (2006) analyzed breast cancer prognosis data obtained from the Swedish death registry, for cases in this study, for association with HRT use. In line with the observational studies reviewed by Antoine et al (2004), Rosenberg (2006) reported a positive association between HRT use and favorable prognostic factors. In particular, associations were found between tumor size and grade.…”
Section: Applicationmentioning
confidence: 53%
“…There is also clear evidence of a dosage effect of HRT on risk (See Figure 3 in Million Women Study Collaborators (2003)). Many recent studies have investigated the relationship between HRT use and prognosis in breast cancer patients; see Antoine et al (2004) for an overview. Most of these studies reported HRT to be associated with a favorable prognosis.…”
Section: Introductionmentioning
confidence: 99%